Overexpression of VrPDF1 gene confers resistance to weevils in transgenic mung bean plant - Thao, Hoang Thi; Ngoc Lan, Nguyen Thi; Son, Le Van; Hoang Mau, Chu (PeerJ Preprints, 2017)
Plant defensins are known for different biological functions such as insect resistance, antibacterial, antifungal and antiviral activities. The role of plant defensins against weevils is based on inhibitor of alpha-amylase activity in weevil gut, therefore, weevils can not digest starch and then die. The low content of Vigna radiata plant defensin 1 (VrPDF1) in mung bean seeds is promted researches to increase the VrPDF1content, in which leads to enhance alpha-amylase inhibition and improve bruchid resistance in mung bean. This article presents the results of overexpression of VrPDF1 gene in transgenic mung bean plants. VrPDF1 gene was successfully transferred into DX22 mung bean cultivar and expressed in T1 generation transgenic mung bean seeds. The extract containing recombinant VrPDF1 protein inhibited alpha-amylase of weevil larvae in its larval stage. The performance of alpha-amylase inhibitor of DX1-3 and DX1-7 transgenic mung bean lines increased by 166.40% and 178.19% respectively, in comparison with non-transgenic plants. The enhancement of alpha-amylase inhibitor ability of rVrPDF1 extracted from transgenic plants is scientifically fundamental to confirm the effectiveness of the application of gene technology in enhancement the ability of mung bean weevil resistance in particular and grain crops in general revenue.
Keywords: mung bean weevil; alpha-amylase inhibitor; Vigna radiata; transgenic mung bean; VrPDF1 gene